Engineered T cell extracellular vesicles displaying PD-1 boost anti-tumor immunity. (October 2022) - Li, Baoqi; Fang, Tianliang; Li, Yuan; Xue, Tianyuan; Zhang, Zhirang; Li, Liyan; Meng, Fanqiang; Wang, Jinqiang; Hou, Linlin; Liang, Xin; Zhang, Xudong; Gu, Zhen
Abstract: Programmed cell death ligand 1 (PD-L1) attenuates the T lymphocytes' response to tumor cells in various malignancies. Extracellular vesicles (EVs) secreted by effector T cells possess potential as anticancer therapeutics by interaction with tumor cells. Here, we constructed T cell derived EVs which display PD-1, the receptor of PD-L1, on the surface to enhance tumor elimination by interrupting PD-1/PD-L1 pathway. Proteomics analysis indicates that the expression of proteins involved in cytotoxicity, T cell receptor signaling pathway and cell binding were upregulated in PD-1 overexpressing exosomes compared to that of microvesicls. PD-1 expressing EVs (PD-1 EVs) neutralize PD-L1 and effectively reinvigorate the activity and proliferation capacity of CD8 + effector T cells. Moreover, PD-1 EVs may also directly attack tumor cells by Fas ligand (FasL) and granzyme B (GzmB). Graphical Abstract: ga1 Highlights: ● Genetically engineered T cell to produce extracellular vesicles (T-EVs) displaying PD-1 for blockade of PD-L1 on cancer cells. ● T-EVs contained cytotoxic molecules that could directly induce cancer cell apoptosis. ● PD-1 expressing T-EVs reinvigorated tumor infiltrating CD8 + T lymphocytes that intensively suppressed tumor progress.